2014
DOI: 10.1080/01443410.2014.895294
|View full text |Cite
|
Sign up to set email alerts
|

Mental toughness in education: exploring relationships with attainment, attendance, behaviour and peer relationships

Abstract: 2015) Mental toughness in education: exploring relationships with attainment, attendance, behaviour and peer relationships, Educational Psychology, 35:7, 886-907,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 53 publications
6
68
0
Order By: Relevance
“…see also McGeown et al, 2015). This finding is also consistent with the results of St Clair- Thompson et al (2014), who found relationships between interpersonal confidence and adolescents peer relationships.The findings of study 2 also revealed higher levels of mental toughness in males than in females (see also Crust et al, 2014), along with higher levels of personal-emotional adjustment. This is consistent with the findings of Wintre and Sugar (2000) using the Student Adaptation to College Questionnaire.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…see also McGeown et al, 2015). This finding is also consistent with the results of St Clair- Thompson et al (2014), who found relationships between interpersonal confidence and adolescents peer relationships.The findings of study 2 also revealed higher levels of mental toughness in males than in females (see also Crust et al, 2014), along with higher levels of personal-emotional adjustment. This is consistent with the findings of Wintre and Sugar (2000) using the Student Adaptation to College Questionnaire.…”
supporting
confidence: 82%
“…Mental toughness describes a set of attributes related to how people deal with challenges, stressors, and pressure. It has been frequently related to successful sport performance (Bull, Shambrook, James, & Brooks, 2005; Connaughton, Wadey, Hanton, & Jones, 2008; Jones, Hanton, & Connaughton, 2007).Recent work has suggested that it may also be a valuable construct to consider within educational settings (Crust, Earle, Perry, Earle, Clough, & Clough, 2014;McGeown, St Clair-Thompson, & Clough, 2015;St Clair-Thompson, Bugler, Robinson, Clough, McGeown, & Perry, 2014).Several theoretical models of mental toughness have been proposed (e.g., Gucciardi, Gordon, & Dimmock, 2009; Jones et al, 2007). However, the model that perhaps offers the most parsimonious account of mental toughness (Weinberg & Gould, 2007) was provided by Clough, Earle, and Sewell (2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite empirical investigations in non-sporting contexts (e.g., Gerber et al, 2012;Gerber, Kalak et al, 2013;Gucciardi et al, 2015;St. Clair-Thompson et al, 2015), lay perceptions of mental toughness remain relatively unexplored.…”
Section: Overall Discussionmentioning
confidence: 99%
“…Although sport has been a predominant focus, empirical research suggests that the benefits of mental toughness extend to a variety of non-sporting populations (Crust, 2007;Gerber et al, 2012;Gerber, Kalak et al, 2013;Gucciardi & Jones, 2012;Gucciardi, Hanton, Gordon, Mallett, & Temby, 2015;St. Clair-Thompson, Bugler, Robinson, Clough, McGeown & Perry, 2015).…”
Section: Introductionmentioning
confidence: 99%